THE VALUES OF EDUCATION IN THE NOVELS âSERIALS OF ANAK-ANAK MAMAKâ BY TERE LIYE A STUDY OF STRUCTURAL SEMIOTICS - Madusari, Endah Ariani; Emzir, E (PPs UNJ, 2015)
The purpose of this study is to discover the values of education in the novels